2018
DOI: 10.21037/atm.2018.10.48
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between surgeon volume and outcomes in spine surgery: a dose-response meta-analysis

Abstract: Background: The relationship between surgeon volume and outcomes in spine surgery is unclear and published studies report inconsistent results. Therefore, a dose-response meta-analysis was conducted to clarify the influence of surgeon volume on outcomes in spine surgery.Methods: PubMed, Embase, and The Cochrane Library were systematically searched without language limitation for observational studies which investigated the relationship between surgeon volume and outcomes in spine surgery. The primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…This is an important point as previous literature has often demonstrated lower perioperative morbidity,3–5 but has failed to examine long term outcomes and PRO as a result of surgeon experience in lumbar fusion. Similarly, higher surgeon volume has been historically associated with lower morbidity18–20 and demonstrated statically significant positive correlation with likelihood of achieving MCID after lumbar fusion in this study. In addition to these traditional surgeon factors, concordance with evidence-based indications for lumbar fusion (NASS criteria) were examined for effects on patient outcomes when comparing surgeons.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This is an important point as previous literature has often demonstrated lower perioperative morbidity,3–5 but has failed to examine long term outcomes and PRO as a result of surgeon experience in lumbar fusion. Similarly, higher surgeon volume has been historically associated with lower morbidity18–20 and demonstrated statically significant positive correlation with likelihood of achieving MCID after lumbar fusion in this study. In addition to these traditional surgeon factors, concordance with evidence-based indications for lumbar fusion (NASS criteria) were examined for effects on patient outcomes when comparing surgeons.…”
Section: Discussionsupporting
confidence: 63%
“…Another traditional variable correlating with many surgical outcomes is surgeon volume. [9][10][11][12] Although many fields have associated surgeon volume with improved outcomes; scoliosis surgery, 13,14 anterior cervical discectomy and fusion, [15][16][17] and lumbar fusions [18][19][20] have also seen fewer complications and lower length of stay associated with higher surgeon volume. Recent studies have even attempted to establish benchmarks for surgeon volume to decrease odds of perioperative complications.…”
mentioning
confidence: 99%
“…However, it is worth mentioning that these features are comparable to those of prior similar reports in the spinal fusion literature. 5,6,18,34,35 Several reports have shown that surgeon experience (as indicated by number of years in practice) 36 and case volume 37 correlate with the accuracy rate of freehand pedicle screw placement and postoperative outcomes. Therefore, Copyright r 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous reports in the literature demonstrate a relationship between greater surgical volume and decreased complication rates for both ACDF and spinal procedures overall. 31,32 In a survey study of orthopaedic surgical resident perspectives on case minimums and preparation for post-residency practice, spinal cases were among the most frequently cited as needing more experience with as the volume of cases were less than other orthopaedic surgical procedures. 33 The present study demonstrated significant reductions in both admission to operation time and operation time of ACDF performed for myelopathy.…”
Section: Discussionmentioning
confidence: 99%